Eksplorasi Engagement Rate dan Strategi Konten Tiktok Tasya Farasya: Validasi Model Komunikasi Pemasaran Digital - Saputra, Rikky; Syahrani, Zahra; Rahmadani, Silviana; Prihadi, Deddy (Journal of Management, Education and Communication, 2025)
This research aims to explore the engagement rate and TikTok content strategy used by Tasya Farasya as a beauty influencer, and relate it to the validation of the digital marketing communication model. This research uses the media text analysis method. This research aims to explore the engagement rate and TikTok content strategy used by Tasya Farasya as a beauty influencer, and relate it to the validation of the digital marketing communication model. The results showed that the content strategy applied included personal branding, utilization of TikTok trends, storytelling, active interaction with followers, and consistency of visual editing. Meanwhile, the engagement rate managed to increase to 3.73%, with an average of 156.5 thousand likes, 1,000 comments, and 2.1 million viewers per content. This figure is classified in the high engagement category. The high engagement rate is proven to be in accordance with the application of elements from the digital marketing communication model, such as source credibility, message suitability, and platform selection.